CUSTOMER VALUE IN USING ELECTRONIC BANKING (WHAT THE MILLENNIAL GENERATION SAY ABOUT “CUSTOMER VALUE” OF USING ELECTRONIC BANKING) - Endang PB; Ali Masjono (Account : Jurnal Akuntansi, Keuangan dan Perbankan, 2019)
ABSTRACT  The changing from human services to electronic services affects the millennialgeneration activities. Electronic banking services give the rise customer value, and electronicbanking provided by a reputation bank increase the pride of using the services.  Banksservices without human’s interaction can increase customer value or benefits.  Theseconclusion raise from the survey of 216 millennial respondents, age between 20 to 35 yearsold who use gadget for daily activities and interaction with the bank.Keywords: Electronic Banking, Customer Value, Cost of Service, and Technology                     Advancement, Pride ABSTRAK  Perubahan bentuk layanan perbankan dari berbasis kepada layanan yang dilakukanoleh manusia kepada layanan berbasis mesin, telah memberikan dampak kepada generasimilenial. Jasa layanan elektronic banking telah memberikan nilai atau makna (customerValue) kepada para pengguna jasa layanan elektronik banking yang disediakan olehperbankan nasional bereputasi. Layanan electronic banking telah meningkatkan kebanggaanmenggunakan layanan tersebut, terutama untuk para generasi milenial yang di surveisebanyak 216 nasabah dan berumur antar 20-35 tahun.Keywords: Electronic Banking, Customer Value, Cost of Service, and Technology                   Advancement, Pride A prominent phenomenon in